Young Adults' Social Relationships Affect Their Likelihood of Ruminating About Past School‐Age Victimization - Malamut, Sarah T.; Salmivalli, Christina (Wiley, 2026)
Rumination about past victimization as an adult underlies the link between school-age victimization and mental health difficulties in young adulthood. Yet, there is a lack of knowledge regarding the risk factors for adults to ruminate on their past victimization experiences. The current study fills this gap by examining whether current social relationships (e.g., workplace victimization, loneliness, romantic relationship satisfaction) of young adults play a role in rumination (as an adult) on past victimization. This preregistered study uses longitudinal data from 1772 Finnish individuals (Mage = 26.04, SD = 1.57), who were part of a large longitudinal project when they were in Grades 4–9, with a follow-up study conducted over a decade later. Workplace victimization and loneliness in adulthood emerged as key predictors of rumination in adulthood about past victimization. The findings suggest that current adult social relationships are a risk factor for previously victimized individuals to dwell on their victimization as adults, regardless of the extent to which they were victimized in adolescence.